2017
DOI: 10.3233/bme-171643
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan: A promising polymer for cartilage repair and viscosupplementation

Abstract: Osteoarthritis (OA) is a painful, degenerative and inflammatory disease that affects the entire synovial joints. Nowadays, no cure exists, and the pharmacological treatments are limited to symptoms alleviation. There is a need for a new efficient and safe treatment. Viscosupplementation is a process that aims to restore the normal rheological properties of synovial fluid. For the past years, hyaluronic acid was usually used but this molecule has some limitations including the short residency time in joint cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Although many preclinical and clinical studies evaluating the efficacy and safety of HA, showed that it is an established treatment for knee OA, its rapid clearance and the short residency time in joint cavity limits its use . Nowadays, preclinical research is focusing on the evaluation of new treatments and molecules able to prevent or delay cartilage degradation . In this contest, chitosan seems to be an interesting candidate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although many preclinical and clinical studies evaluating the efficacy and safety of HA, showed that it is an established treatment for knee OA, its rapid clearance and the short residency time in joint cavity limits its use . Nowadays, preclinical research is focusing on the evaluation of new treatments and molecules able to prevent or delay cartilage degradation . In this contest, chitosan seems to be an interesting candidate.…”
mentioning
confidence: 99%
“…Chitosan, a partially deacetylated derivative from chitin, composed of D‐gucosamine and N‐acetylglucosamine, is structurally similar to glycosaminoglycans . Due to its ability to interact with negatively charged cell surfaces, chitosan is extensively applied to prepare nanocarriers for different applications in the biomedical field . Several preclinical studies suggested that chitosan has a chondroprotective effect and is able to increase chondrocyte proliferation, expression of cartilage matrix components and reduce inflammatory and catabolic mediators following i.a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The development of acellular polymers may provide an attractive alternative to overcome the cost and complexity of cell‐based approaches . Chitosan is one of the most widely investigated polymers for regenerative medicine, in particular for cartilage regeneration because it displays structural properties that are similar to natural glycosaminoglycans . Chitosan promotes the expression of cartilage matrix compounds and reduces production of inflammatory and catabolic mediators by chondrocytes .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, chitosan is a promising natural biomaterial scaffold for cartilage defect repair. 35 Furthermore, the positive charge on chitosan could facilitate scaffold binding to negatively charged tissue cells or body uid.…”
mentioning
confidence: 99%